The Risk-Adjusted Impact of Intraoperative Hemofiltration on Real-World Outcomes of Patients Undergoing Cardiac Surgery - BM, Matata; M, Shaw (Journal of Clinical Nephrology, 2017)
Objectives: The role of perioperative hemofiltration (HF) in adult patients with impaired renal function undergoing cardiac surgery is controversial. There are suggestions that it may be beneficial for high risk patients undergoing prolonged cardiopulmonary bypass (CPB) surgery. However, long term outcomes in coronary artery bypass graft (CABG) surgery patients have not been investigated. Methods: To address this we retrospectively followed 7620 patients who underwent CABG between April 2001 and March 2006. Logistic regression was used to risk adjust in-hospital outcomes. Cox proportional hazards analysis was used to risk adjust Kaplan-Meier freedom from death curves. Outcomes were adjusted for American Heart Association and American College of College of Cardiology recommended variables. Results: 113 patients had intraoperative HF, 38 had postoperative HF and control group of 7006 that had no HF. After adjusting for differences in case-mix, patients with preoperative kidney disease who received postoperative HF proportionately had significantly higher rates of hospital deaths as compared with intraoperative HF patients. In addition, 5-year follow-up risk-adjusted freedom from death indicated significant differences between intraoperative HF group and postoperative HF patients. Conclusions: These findings support the hypothesis that after adjusting for differences in case mixes, the use of intraoperative hemofiltration may offer superior short term clinical outcomes and longer-term survival benefits for patients with preoperative kidney disease.